Academic English in Exile:Mapping the Research PublicationChallengesof Displaced Ukrainian Scholars in the UK - Torubara, Oksana (Lesya Ukrainka Volyn National University, 2025)
For displaced Ukrainian scholars fleeing war and continuing their research abroad, English has rapidly shifted from a foreign language to the primary medium of institutional integration, academic visibility, and professional continuity. In this context, effective research dissemination increasingly depends on advanced competence in English for Research Publication Purposes (ERPP). This study investigates how displaced Ukrainian researchers, hosted in the United Kingdom through the British Academy's Researchers-at-Risk (RaR) programme, navigate academic writing in English, focusing on how their language proficiency, prior international exposure, and professional experience shape their ability to meet the demands of international research communication. A survey, conducted in October - November 2024 with 125 RaR fellows examined participants self-reported CEFR-aligned proficiency levels, international mobility experience, certification profiles, and engagement with core academic writing tasks in English. Although many reported high general proficiency and held international language certificates, this did not always translate to strong ERPP skills. Even those with a strong track record of academic writing faced challenges with disciplinary genres, rhetorical structure, and literature synthesis. The findings highlight a clear distinction between general English competence and specialised skills needed for research publishing. While participants regularly engaged in writing emails, abstracts, and conference presentations, many struggled with article structuring, source synthesis, and referencing. Institutional support, where available, was often limited or insufficiently targeted. These insights underscore the need for tailored, discipline sensitive ERPP support to enable meaningful academic participation in exile.
Keywords: Ukrainian academics; Academic writing; displaced scholars; English for Research Publication Purposes (ERPP)